(untitled) (Journal of the College of Basic Education, 2023)
The current research problem is summarized in (what conditionality is imposed by balances and its role inindustrial product design).Therefore, the research aims to identify the types of balances and their conditionality in product design.The research has dealt with the meaning and types of balances in the design in general and in the productThen the balances and their conditionalities in the design of the industrial product were discussed.The research reached a number of results that achieve the goal of the research.• Problem / What is the conditionality imposed by the balances and their role in the design of the industrial product?• Aim / stand on the types of balances and conditionalities in the design of the industrial product.ForewordThe sense of equilibrium is innate and we notice it in the world around us.It means a distortion of something and a lack of comfort. And that the Great Creator created everything and fashioned everything increation system and were not in its limbs, but rather in its shapes, colors and types.And God Almighty said in His Holy Book Have We not made the earth a cradle * and the mountains as pegs 78)Al-Naba’ verse 6-7 (in presenting some of the miracles in the universe.It maintains the balance of the earth, so it does not deviate or become disturbed. Maintaining balance is achieved in various ways.It is a balance between the external pressure on the earth’s surface and the internal pressure in its interior.It varies from one place to another. Or the protrusion of mountains in a place is equivalent to the subsidence of the land.in another location. It has been scientifically proven that mountains have roots in the depths of the earth and their function is to protectits layers from moving, and maintaining its balance, as the solid layer of the earth’s crust lies onA soft slippery layer even if the bottom surface of the hard layer is level and the same as the upper surface of the layer.The soft earth would have slipped from under our feet and our houses, and would have tilted, and when it had settled for us, it would have settled, and it would not have been right.land to live on. Science has proven that the mountains are embedded in the ground to carry out a mission.The fixing is the same as the peg for the tent, and only one-third of it is visible, and two-thirds is inside.